2009
DOI: 10.1063/1.3222914
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in the field sensitivity of magnetoelectric laminate heterostructures

Abstract: ). Das, J.; Gao, J.; Xing, Z.; et al., "Enhancement in the field sensitivity of magnetoelectric laminate heterostructures," Appl. Phys. Lett. 95, 092501 (2009); http:// dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
70
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 13 publications
(13 reference statements)
1
70
1
2
Order By: Relevance
“…3,4 To date, ME laminated composites of magnetostrictive Metglas foils and piezoelectric Pb(Zr,Ti)O 3 or PZT have been widely investigated in various operational modes and optimized for use in magnetic field detection applications. [5][6][7] Highly sensitive, room temperature, passive magnetic field sensors have been developed based on ME laminates. Such magnetic sensors have been shown to have noise floors on the order of pT/HHz for Metglas/PZT foil laminates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 To date, ME laminated composites of magnetostrictive Metglas foils and piezoelectric Pb(Zr,Ti)O 3 or PZT have been widely investigated in various operational modes and optimized for use in magnetic field detection applications. [5][6][7] Highly sensitive, room temperature, passive magnetic field sensors have been developed based on ME laminates. Such magnetic sensors have been shown to have noise floors on the order of pT/HHz for Metglas/PZT foil laminates.…”
mentioning
confidence: 99%
“…The electrode pattern allowed for a symmetrical polling of the piezoelectric fibers in a back-to-back manner along their length axes. 5 Three layers of Metglas foils cut into dimensions of 8 cm  1 cm  22 lm were then attached to the upper and lower surfaces of the Kapton V R electrodes using the same epoxy. Figure 1 shows the ME voltage (a ME ) and charge (a me ) coefficients of the Metglas/PZT-fiber sensor as a function of DC magnetic field H dc at room temperature.…”
mentioning
confidence: 99%
“…The calibration technique for such measurements has been previously detailed in Ref. 4. Part ͑b͒ shows the noise level and sensitivity results, as indicated.…”
mentioning
confidence: 99%
“…Such ME structures contain magnetic and electric materials that are in close contact with each other. It has been shown that coupling between the magnetic and electric phases can offer control of the magnetic/electric responses under electric/magnetic field, 3,4 for example, through stress tuning. High ME coupling between constituent magnetostrictive and and piezoelectric phases in the stress tuned structures allows the possibility of achieving both types of cross-tuning: control of magnetism via an electric field, and control of electric polarization through the application of a magnetic field.…”
mentioning
confidence: 99%
See 1 more Smart Citation